FACTORS ASSOCIATED WITH MALARIA PREVALENCE AMONG UNIVERSITY STUDENTS AT LIRA UNIVERSITY TEACHING HOSPITAL, LIRA CITY. A CROSS-SECTIONAL STUDY. - Ashaba, Nasser; Atai, Janet Mary; Murungi, Tom; Layet, Florence; Musinguzi, Marvin; Amito, Freda; Akello, Anne Ruth; Kigongo, Eustes; Opollo, Marc Sam (Student’s Journal of Health Research Africa, 2025)
Background Malaria is a leading cause of death and disease in many developing countries. Lira district remains an endemic area for malaria in Uganda, greatly impacting the lives of many. The study investigated the factors associated with Malaria prevalence among Lira University students at Lira University Teaching Hospital, Lira City. Methodology A cross-sectional mixed methods study was conducted among 340 participants between March and April 2023. Participants were sampled by convenience sampling and data was collected using an interviewer-administered questionnaire. Data was entered and analyzed in SPSS version 26 at univariate, bivariate, and multivariate levels. Binary logistic regression both at bivariate and multivariate analysis was done. Qualitative data was collected from 16 purposively sampled participants using an in-depth interview guide and was analyzed manually through thematic content analysis. Results A total of 340 participants were recruited, achieving a 100% response rate. The majority 248(76.5%) of the participants were aged 18-24. Half, 165(50.9%) were males, most, 263(81.2%) were single, and 208(64.2%) were unemployed. About a third, 119(36.7%) and 121(37.3%) were Anglicans and were from the Faculty of Nursing and Midwifery respectively. The prevalence of malaria among the students was 13.3% (95% CI=9.6 - 16.99). The factors associated with the malaria prevalence were; staying around bushy areas (AOR: 2.03; 95% CI: 1.05-3.92) and use of mosquito repellants (AOR: 2.09; 95% CI: 1.09-4.04). Qualitatively, most participants reported bushy environments and stagnant water to be contributing to the high prevalence. Conclusion The prevalence of malaria among students was 13.3%. The study starkly illustrates that mosquito repellents provide little to no protection against malaria, whereas lingering near overgrown, bushy areas significantly heightens the risk of contracting the disease. Recommendation There is a need for a wide-ranging and coordinated approach to malaria prevention and control, encompassing environmental management and personal protective measures.